Legacy effects of crop diversity on weed-crop competition in maize production - Uriel D. Menalled; K. Ann Bybee-Finley; Richard G. Smith; Antonio DiTommaso; Heather M. Darby; Sarah J. Pethybridge; Matthew R. Ryan (npj Sustainable Agriculture)
Abstract The legacy effects of crop diversity on maize (Zea mays L.) tissue nutrient composition, weed community structure, and intensity of weed-crop competition were assessed through a field experiment at two sites in the northeastern United States. Fields were conditioned with crop diversity gradients from summer 2016 to spring 2019. The crop diversity gradients ranged from a single cultivar to sixteen intercropped cultivars (four species, four cultivars per species) and were established in organic annual and perennial cropping systems. Following the three-year conditioning phase, maize was planted across the entire experiment, and each conditioning-phase diversity treatment was split into weed-free, ambient-weed, moderate-weed, and heavy-weed treatments. Within each cropping system, the effect of crop diversity legacy on weed-crop competition was negligible. In contrast, weed-crop competition varied between the maize grown in soil conditioned by the annual and perennial cropping systems.